The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/genes12071083
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Hsm3 Protein Function in Yeast Saccharomyces cerevisiae NuB4 Complex

Abstract: In the nuclear compartment of yeast, NuB4 core complex consists of three proteins, Hat1, Hat2, and Hif1, and interacts with a number of other factors. In particular, it was shown that NuB4 complex physically interacts with Hsm3p. Early we demonstrated that the gene HSM3 participates in the control of replicative and reparative spontaneous mutagenesis, and that hsm3Δ mutants increase the frequency of mutations induced by different mutagens. It was previously believed that the HSM3 gene controlled only some mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Previous studies have shown that the genes HAT1 , HIF1, and HSM3 , encoding subunits of the NuB4 complex, participated in the control of replicative and reparative spontaneous mutagenesis [ 36 , 55 , 58 ]. In these experiments, hat1Δ mutation epistatized to hsm3Δ and hif1Δ .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that the genes HAT1 , HIF1, and HSM3 , encoding subunits of the NuB4 complex, participated in the control of replicative and reparative spontaneous mutagenesis [ 36 , 55 , 58 ]. In these experiments, hat1Δ mutation epistatized to hsm3Δ and hif1Δ .…”
Section: Resultsmentioning
confidence: 99%
“…At high doses of UV, rad30Δ mutation completely suppressed hsm3 - and hif1 -specific mutagenesis [ 36 ]. We assumed that a similar interaction would also be observed in the asf1Δ rad30Δ double mutant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations